Climate-Smart Agriculture Investment Cost-Benefit Model - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
ICRAF with Probability Management developed the MS Excel-based Climate-Smart Agriculture Investment Plan Cost-Benefit Tool. This tool uses probabilistic approaches and modern portfolio theory to predict the performance of agriculture investments in the face of climate and social risks. It has been used in developing plans for Ghana and Burkina.